A method for refining pyromellitic acid
Patent Information
- Application Number
- CN202610977125.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-07-02
- Publication Date
- 2026-10-30
AI Technical Summary
该方法虽然能实现均苯四甲酸和偏苯三甲酸的分离,但存在流程长、吸附剂和萃取剂用量大、回收溶剂能耗高问题
本发明方法可将均苯四甲酸粗品纯度提高,而且收率较高,产品纯度达到99%以上,收率达到95%以上;由于重结晶液中未完全析出的均苯四甲酸被树脂吸附并回收,废水中的有机物含量降低90%以上,处理难度降低。
Smart Images

Figure CN123003401A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of chemical separation, and in particular to a method for purifying pyromellitic acid. Background Technology
[0002] Pyromellitic acid (PMA) is an important fine chemical intermediate widely used in the synthesis of polyimide (PI), epoxy resin curing agents, dyes, and functional materials. Its high-purity products hold an irreplaceable position, especially in high-performance polymer materials. Currently, industrially, PMA is mainly prepared from durene via gas-phase oxidation and liquid-phase oxidation methods, requiring further complex purification processes to meet the demands of high-end applications.
[0003] The gas-phase oxidation method involves reacting mesitylene in a gaseous state with air or oxygen-enriched gas on the surface of a solid catalyst at high temperatures (typically 350-450°C) to directly produce pyromellitic dianhydride (PMDA). This method typically employs a fixed-bed reactor, and the catalyst is often a composite oxide system containing metal oxides such as vanadium and molybdenum. The resulting pyromellitic dianhydride is usually a gaseous mixture that requires cooling and collection steps, followed by hydrolysis and purification to obtain refined pyromellitic dianhydride.
[0004] Liquid-phase oxidation involves reacting mesitylene with oxygen or air in a solvent (such as acetic acid, water, or a mixture thereof) in the presence of a metal salt catalyst such as cobalt or manganese to produce pyromellitic acid (PMA). Unlike gas-phase oxidation, liquid-phase oxidation can achieve efficient oxidation under mild conditions of 100-200℃, producing a liquid or solid product, which can be purified to obtain refined pyromellitic acid. Due to its low reaction temperature and good product selectivity, the liquid-phase method has promising prospects for industrialization.
[0005] The crude pyromellitic acid obtained by gas-phase and liquid-phase oxidation methods has a complex composition. Besides the target product, pyromellitic acid, it often contains incompletely oxidized intermediates such as trimellitic acid and methyltricarboxylic acid, decarboxylation products, and carbonization byproducts. Furthermore, catalyst metal impurities may also be present. Polyimide, as a high-performance engineering plastic and film material, is widely used in aerospace, microelectronics, and flexible displays, requiring extremely high purity of its monomers. Pyromellitic acid is a precursor for the synthesis of pyromellitic dianhydride (PMDA), which is a key dianhydride monomer in the preparation of polyimide. If it contains metal ions (such as Co...), it may cause serious contamination. 2+ Mn 2+ Fe 3+Colored impurities or oxidation byproducts can trigger side reactions during polymerization, affecting molecular chain growth, reducing the degree of polymerization, and leading to decreased mechanical properties, yellowing, or reduced thermal stability of the material. Therefore, the purity of pyromellitic acid used in polyimide synthesis typically needs to reach above 99%, the total content of metallic impurities should be below 10 ppm, and it must not contain any active impurities that affect the polymerization reaction.
[0006] Although existing technologies have enabled the industrial production of pyromellitic acid (PMA), several shortcomings remain in the refining process. Chinese invention patent CN 118146235A discloses a method for improving the purity of PMA through hydrolysis and recrystallization. First, the raw material is dissolved in hot water at 90°C to obtain an aqueous PMA solution. After filtration and cooling crystallization, the PMA product is obtained, with a yield of 45.9-87.9 wt% and a maximum purity of 99.03%. Chinese invention patent CN 119823141A adds organic solvents such as acetonitrile, N,N-dimethylformamide, and dimethyl sulfoxide during the hydrolysis to PMA process, followed by further purification. This yields PMA with a yield of 67.3-84.0 wt%, but requires the recovery of the organic solvents. Japanese patent publication JPH03294272A describes dissolving crude PMDA in twice the volume of deionized water to obtain an aqueous PMA solution. This solution is then refluxed and stirred at 150-200°C for 1 hour, followed by hot filtration and cooling crystallization to obtain white crystalline PMA with a yield of 62.5%. However, existing recrystallization techniques suffer from low product yields. This is mainly because pyromellitic acid and its impurities, such as trimellitic acid and methyltricarboxylic acid, have structural similarities. These impurities readily form hydrogen-bonded networks with pyromellitic acid, disrupting its structural regularity and making it difficult to precipitate from the aqueous system. Consequently, pyromellitic acid is lost with wastewater discharge. Furthermore, some pyromellitic acid complexes with metals to form precipitates, which are removed along with activated carbon during filtration, further reducing the yield.
[0007] Trimericacrylic acid is one of the main impurities in the production of pyromellitic acid. Chinese invention patent CN107286014 B discloses a method for separating a mixture of pyromellitic acid and trimellitic acid. The method mainly involves adding an amine-containing solid adsorbent to an acetone solution of the mixture. The solid adsorbent adsorbs the pyromellitic acid to form a solid mixture, while the trimellitic acid remains in the solution without reacting. The solid mixture and solution are then filtered, and the filtrate and solid mixture are collected. These are then added to an extraction solvent, and finally, the extraction solvent is evaporated to obtain purified pyromellitic acid. While this method can achieve the separation of pyromellitic acid and trimellitic acid, it suffers from problems such as a long process, large amounts of adsorbent and extractant used, and high energy consumption for solvent recovery.
[0008] In conclusion, there is an urgent need to improve the purification yield of pyromellitic acid and simplify the process to reduce purification costs. Summary of the Invention
[0009] In order to overcome the shortcomings of low product yield and long refining process in the prior art, the present invention provides a refining method for pyromellitic acid, which can achieve a refining product yield of more than 95%.
[0010] The present invention is achieved by the following technical solution.
[0011] A method for purifying pyromellitic acid includes the following steps: S1. Mix crude pyromellitic acid raw material with inorganic acid solvent at a mass ratio of 1:1~10, heat to 60~100℃ under stirring, and reflux for 1~3h until pyromellitic acid is completely dissolved to form a solution; S2. Add 2-5% activated carbon powder according to the raw material mass, continue to reflux and stir for 1-3 hours, filter off the activated carbon while hot, cool the filtrate to 5-40℃ at 10-60℃ / h to precipitate pyromellitic acid crystals (crystals account for 90-99% of all pyromellitic acid), and then wash and dry with demineralized water to obtain the refined pyromellitic acid product. S3. After adjusting the pH of the recrystallization solution (in which 1-10% of the pyromellitic acid remains unprecipitated) to 2-5, adsorb the remaining pyromellitic acid in the recrystallization solution using an adsorption column bed (the recrystallization solution is strongly acidic after pH adjustment; under acidic conditions, the resin bed has a higher adsorption selectivity for pyromellitic acid than other organic carboxylic acids, but cannot adsorb other organic carboxylic acids). Then, adjust the pH of the adsorbed solution to 7-9, and use another adsorption column bed filled with the same adsorbent to adsorb other organic carboxylic acids (neutral and weakly alkaline conditions are favorable for the adsorption of other carboxylic acids into the resin bed). After adsorption saturation, elute the pyromellitic acid from the first adsorption column with sodium hydroxide aqueous solution. Add hydrochloric acid to the eluent to adjust the pH to 5-7. The precipitate is then washed with water and dried to obtain the purified pyromellitic acid product, which is recovered together with the pyromellitic acid precipitated from recrystallization in step S2.
[0012] By adopting the above technical solution, the present invention uses inorganic acid as a recrystallization solvent, which can improve the yield of precipitated pyromellitic acid product; in addition, the inorganic acid dissociates and dissolves the insoluble matter formed by pyromellitic acid and impurities, thereby improving the purity of the precipitated pyromellitic acid crystals and increasing the yield; finally, the resin is used to adsorb the incompletely precipitated pyromellitic acid and other organic carboxylic acids in the recrystallization solution to recover almost all of the pyromellitic acid.
[0013] Furthermore, in step S1, the crude pyromellitic acid raw material is obtained by liquid-phase oxidation or gas-phase oxidation. The crude acid raw material of this invention can be obtained by liquid-phase oxidation. Crude acid raw materials obtained by liquid-phase oxidation typically contain metal salts such as Co and Mn, as well as bromides. Other organic carboxylic acid components, such as trimellitic acid and methyltricarboxylic acid, are similar to those obtained by gas-phase oxidation. Therefore, this invention is also applicable to processing crude acid raw materials obtained by gas-phase oxidation.
[0014] Furthermore, in step S1, the inorganic acid solvent is an aqueous solution containing an inorganic acid with a concentration of 1-15%; the inorganic acid is selected from at least one of hydrochloric acid, nitric acid, phosphoric acid, and sulfuric acid.
[0015] Preferably, in step S1, the mass ratio of crude pyromellitic acid raw material to inorganic acid solvent is 1:2~6.
[0016] Preferably, in step S1, after the crude pyromellitic acid raw material is mixed with the inorganic acid solvent, the heating temperature is 80~95℃ and the reflux time is 1~2h.
[0017] Preferably, in step S2, the filtrate after removing activated carbon is cooled to 5-30°C at a rate of 10-30°C / h.
[0018] Furthermore, in step S3, the resin particles packed in the adsorption column are selected from macroporous styrene strong base anion exchange resin or styrene-based resin modified with amine, amide, methoxy or hydroxyl groups.
[0019] Furthermore, in step S3, ammonia water is used to adjust the pH value of the recrystallization solution and the solution obtained after the first adsorption, and the concentration of ammonia water is 20wt%.
[0020] Furthermore, in step S3, the concentration of the sodium hydroxide aqueous solution is 3 wt%.
[0021] Furthermore, in step S3, the concentration of hydrochloric acid is 30 wt%.
[0022] This application has the following beneficial effects: The method of this invention can improve the purity of crude pyromellitic acid and achieve a high yield, with a product purity of over 99% and a yield of over 95%. Since the pyromellitic acid that is not completely precipitated in the recrystallization solution is adsorbed and recovered by the resin, the organic matter content in the wastewater is reduced by more than 90%, and the treatment difficulty is reduced. Attached Figure Description
[0023] Figure 1 This is the HPLC chromatogram of the product obtained in Example 1 of the present invention; Figure 2 This is the HPLC chromatogram of the product obtained in Example 2 of the present invention; Figure 3This is the HPLC chromatogram of the product obtained in Example 3 of the present invention; Figure 4 This is the HPLC chromatogram of the product obtained in Example 4 of the present invention; Figure 5 This is the HPLC chromatogram of the product obtained in Example 5 of the present invention; Figure 6 This is the HPLC chromatogram of the product obtained in Example 6 of the present invention; Figure 7 This is the HPLC chromatogram of the product obtained in Comparative Example 1 of this invention. Detailed Implementation
[0024] The present patent application will be further described below with reference to the embodiments.
[0025] The crude acid raw material used in the following embodiments of this application is mesitylene, which is prepared by air-liquid phase oxidation reaction. The catalytic oxidation reaction system consists of metal salts of Co and Mn, bromide, and acetic acid. Similar preparation methods are described in Chinese invention patents with publication numbers CN117430503 A and CN114369099 A. The main components of the crude acid raw material in this application are 92.2 wt% pyromellitic acid, 1.8 wt% trimellitic acid, 1.7 wt% 5-methyl-1,2,4-benzenetricarboxylic acid, 3.8 wt% metal salt, and 0.5 wt% other impurities.
[0026] Example 1
[0027] 1g of crude acid raw material was added to 4g of 10wt% hydrochloric acid, and the temperature was gradually raised to 90℃ and maintained for 1 hour to dissolve most of the solid raw material. Activated carbon powder, accounting for 5% of the crude acid raw material, was added and maintained for 1 hour. After sufficient adsorption, the activated carbon residue was filtered off while hot. The remaining filtrate was gradually cooled at a rate of 10℃ / h, with a final cooling temperature of 10℃, yielding recrystallized crystals and recrystallization filtrate. The precipitated crystals were washed with 5g of demineralized water and then dried at 120℃ to obtain the refined acid product. The recrystallization filtrate was first adjusted to pH 4 with 20wt% ammonia water and passed through a first bed of styrene resin (Dow IRA-900 type) to adsorb pyromellitic acid. The pH was then further adjusted to 7 with 20wt% ammonia water and passed through a second bed of the same resin to adsorb other organic carboxylic acids at a rate of 5 BV / h (i.e., 5 times the volume of filtrate per hour passes through the resin bed). After the resin was saturated with adsorption, pyromellitic acid was eluted from the first adsorption column with a 3wt% sodium hydroxide aqueous solution. The eluent was then adjusted to pH 7 with 30wt% hydrochloric acid. The precipitate was washed with water and dried to obtain the purified pyromellitic acid product, which was recovered along with the previously recrystallized pyromellitic acid. Product yield and purity are shown in Table 1. Figure 1 .
[0028] Example 2
[0029] 1g of crude acid raw material was added to 4g of 10wt% sulfuric acid, and the temperature was gradually raised to 95℃ and maintained for 1 hour to dissolve most of the solid raw material. Activated carbon powder, accounting for 5% of the crude acid raw material, was added and maintained for 1 hour. After sufficient adsorption, the activated carbon residue was filtered off while hot. The remaining filtrate was gradually cooled at a rate of 5℃ / h, with a final cooling temperature of 5℃, yielding recrystallized crystals and recrystallization filtrate. The precipitated crystals were washed with 5g of demineralized water and then dried at 120℃ to obtain the refined acid product. The recrystallization filtrate was first adjusted to pH 4 with 20wt% ammonia water and passed through a first bed of styrene resin (Dow IRA-900 type) to adsorb pyromellitic acid. The pH was then further adjusted to 7 with 20wt% ammonia water and passed through a second bed of the same resin to adsorb other organic carboxylic acids at a rate of 5 BV / h (i.e., 5 times the volume of filtrate per hour passes through the resin bed). After the resin was saturated with adsorption, pyromellitic acid was eluted from the first adsorption column with a 3wt% sodium hydroxide aqueous solution. The eluent was then adjusted to pH 7 with 30wt% hydrochloric acid. The precipitate was washed with water and dried to obtain the purified pyromellitic acid product, which was recovered along with the previously recrystallized pyromellitic acid. Product yield and purity are shown in Table 1. Figure 2 .
[0030] Example 3
[0031] 1g of crude acid raw material was added to 4g of 10wt% nitric acid, and the temperature was gradually raised to 95℃ and maintained for 1 hour to dissolve most of the solid raw material. Activated carbon powder, accounting for 2% of the crude acid raw material, was added and maintained for 1 hour. After sufficient adsorption, the activated carbon residue was filtered off while hot. The remaining filtrate was gradually cooled at a rate of 5℃ / h, with a final cooling temperature of 5℃, yielding recrystallized crystals and recrystallization filtrate. The precipitated crystals were washed with 5g of demineralized water and then dried at 120℃ to obtain the refined acid product. The recrystallization filtrate was first adjusted to pH 4 with 20wt% ammonia water and passed through a first bed of styrene resin (Dow IRA-900 type) to adsorb pyromellitic acid. The pH was then further adjusted to 7 with 20wt% ammonia water and passed through a second bed of the same resin to adsorb other organic carboxylic acids at a rate of 5 BV / h (i.e., 5 times the volume of filtrate per hour passes through the resin bed). After the resin was saturated with adsorption, pyromellitic acid was eluted from the first adsorption column with a 3wt% sodium hydroxide aqueous solution. The eluent was then adjusted to pH 7 with 30wt% hydrochloric acid. The precipitate was washed with water and dried to obtain the purified pyromellitic acid product, which was recovered along with the previously recrystallized pyromellitic acid. Product yield and purity are shown in Table 1. Figure 3 .
[0032] Example 4
[0033] 1g of crude acid raw material was added to 4g of 10wt% nitric acid, and the temperature was gradually raised to 95℃ and maintained for 1 hour to dissolve most of the solid raw material. Activated carbon powder, accounting for 2% of the crude acid raw material, was added and maintained for 1 hour. After sufficient adsorption, the activated carbon residue was filtered off while hot. The remaining filtrate was gradually cooled at a rate of 5℃ / h, with a final cooling temperature of 5℃, yielding recrystallized crystals and recrystallization filtrate. The precipitated crystals were washed with 5g of demineralized water and then dried at 120℃ to obtain the refined acid product. The recrystallization filtrate was first adjusted to pH 5 with 20wt% ammonia water and passed through a first bed of styrene resin (Dow IRA-900 type) to adsorb pyromellitic acid. The pH was then further adjusted to 9 with 20wt% ammonia water and passed through a second bed of the same resin to adsorb other organic carboxylic acids at a rate of 10 BV / h (i.e., 5 times the volume of filtrate per hour passes through the resin bed). After the resin was saturated with adsorption, pyromellitic acid was eluted from the first adsorption column with a 3wt% sodium hydroxide aqueous solution. The eluent was then adjusted to pH 7 with 30wt% hydrochloric acid. The precipitate was washed with water and dried to obtain the purified pyromellitic acid product, which was recovered along with the previously recrystallized pyromellitic acid. Product yield and purity are shown in Table 1. Figure 4 .
[0034] Example 5
[0035] 1g of crude acid raw material was added to 4g of 10wt% nitric acid, and the temperature was gradually raised to 95℃ and maintained for 1 hour to dissolve most of the solid raw material. Activated carbon powder, accounting for 2% of the crude acid raw material, was added and maintained for 1 hour. After sufficient adsorption, the activated carbon residue was filtered off while hot. The remaining filtrate was gradually cooled at a rate of 5℃ / h, with a final cooling temperature of 5℃, yielding recrystallized crystals and recrystallization filtrate. The precipitated crystals were washed with 5g of demineralized water and then dried at 120℃ to obtain the refined acid product. The recrystallization filtrate was first adjusted to pH 5 with 20wt% ammonia water and passed through a first bed of aminostyrene resin (Dow IRA-94 type) to adsorb pyromellitic acid. The pH was then further adjusted to 9 with 20wt% ammonia water and passed through a second bed of the same resin to adsorb other organic carboxylic acids at a rate of 10 BV / h (i.e., 5 times the volume of filtrate per hour passes through the resin bed). After the resin was saturated with adsorption, pyromellitic acid was eluted from the first adsorption column with a 3wt% sodium hydroxide aqueous solution. The eluent was then adjusted to pH 7 with 30wt% hydrochloric acid. The precipitate was washed with water and dried to obtain the purified pyromellitic acid product, which was recovered along with the previously recrystallized pyromellitic acid. Product yield and purity are shown in Table 1. Figure 5 .
[0036] Example 6
[0037] Except for the use of hydroxyl styrene resin (Dow IRA-761) as the adsorption resin, the other steps and main parameters are the same as in Example 5. Product yield and purity are shown in Table 1. Figure 6 .
[0038] Comparative Example 1 1g of crude acid raw material was added to 4g of pure water, and the temperature was gradually raised to 95℃ and maintained for 1 hour to dissolve most of the solid raw material. Activated carbon powder, accounting for 2% of the crude acid raw material, was added and maintained for 1 hour. After sufficient adsorption, the activated carbon residue was filtered off while hot. The remaining filtrate was gradually cooled at a rate of 5℃ / h, with a final cooling temperature of 5℃, yielding recrystallized crystals and recrystallized filtrate. The precipitated crystals were washed with 5g of demineralized water and then dried at 120℃ to obtain the refined acid product. Product yield and purity are shown in Table 1. Figure 7 .
[0039] Table 1: Key Indicators and Parameters of Each Embodiment
[0040] The embodiments described herein are preferred embodiments of the present invention and are not intended to limit the scope of protection of the present invention. Therefore, all equivalent changes made in accordance with the structure, shape, and principle of the present invention should be covered within the scope of protection of the present invention.
Claims
1. A method for purifying pyromellitic acid, characterized in that: Includes the following steps: S1. Mix crude pyromellitic acid raw material with inorganic acid solvent at a mass ratio of 1:1~10, heat to 60~100℃ under stirring, and reflux for 1~3h until pyromellitic acid is completely dissolved to form a solution; S2. Add 2-5% activated carbon powder by weight of raw materials, continue to reflux and stir for 1-3 hours, filter off the activated carbon while hot, cool the filtrate to 5-40℃ at 10-60℃ / h to precipitate pyromellitic acid crystals, and then wash and dry the filtrate with deionized water to obtain the refined pyromellitic acid product. S3. After adjusting the pH of the recrystallization solution to 2-5, adsorb the incompletely precipitated pyromellitic acid in the recrystallization solution using an adsorption column bed. Then, adjust the pH of the adsorbed solution to 7-9, and use another adsorption column bed filled with the same adsorbent to adsorb other organic carboxylic acids. After adsorption saturation, elute the pyromellitic acid from the first adsorption column with sodium hydroxide aqueous solution. Add hydrochloric acid to the eluent to adjust the pH to 5-7. The precipitated product is then washed with water and dried to obtain the purified pyromellitic acid product, which is recovered together with the pyromellitic acid precipitated from recrystallization in step S2.
2. The method for purifying pyromellitic acid according to claim 1, characterized in that: In step S1, the crude pyromellitic acid raw material is obtained by liquid-phase oxidation or gas-phase oxidation.
3. The method for purifying pyromellitic acid according to claim 1, characterized in that: In step S1, the inorganic acid solvent is an aqueous solution containing an inorganic acid with a concentration of 1-15%; the inorganic acid is selected from at least one of hydrochloric acid, nitric acid, phosphoric acid, and sulfuric acid.
4. The method for purifying pyromellitic acid according to claim 1, characterized in that: In step S3, the resin particles packed in the adsorption column are selected from macroporous styrene strong base anion exchange resin or styrene-based resin modified with amine, amide, methoxy or hydroxyl groups.
5. The method for purifying pyromellitic acid according to claim 1, characterized in that: In step S3, ammonia water is used to adjust the pH value of the recrystallization solution and the solution obtained after the first adsorption. The concentration of ammonia water is 20wt%.
6. The method for purifying pyromellitic acid according to claim 1, characterized in that: In step S3, the concentration of the sodium hydroxide aqueous solution is 3 wt%.
7. The method for purifying pyromellitic acid according to claim 1, characterized in that: In step S3, the concentration of hydrochloric acid is 30 wt%.
Citation Information
Patent Citations
A method for separating a mixture of pyromellitic acid and trimellitic acid
CN107286014B
Method for preparing pyromellitic dianhydride through liquid phase oxidation
CN114369099A
Method for liquid-phase oxidation of durene
CN117430503A
Purification process and application of low-purity pyromellitic dianhydride material
CN118146235A
Refining method of pyromellitic dianhydride
CN119823141A
